The Impact of Financial Literacy on Entrepreneurial Intention: The Mediating Role of Saving Behavior - Alshebami, Ali Saleh; Al Marri, Salem Handhal (Frontiers in Psychology, 2022)
This study investigated the impact of financial literacy (financial awareness) on potential entrepreneurs' intent in Saudi Arabia. It also examined saving behaviour as a mediator in the relationship between financial literacy and entrepreneurial intention. The study's data were collected by an online questionnaire sent to a sample of 270 potential entrepreneurs at Abqaiq Applied College, affiliated with King Faisal University. Data analysis was done using partial least squares structural equation modelling (PLS-SEM). According to the findings, there is no direct relationship between financial literacy and entrepreneurial intent. However, it has been reported that saving behaviour can mediate between financial literacy and entrepreneurial intent. Furthermore, the study's model could explain approximately 45% of the variance in entrepreneurial intention